Strategies to Overcome Foreign Language Reading Anxiety among Globalized EFL Learners - Wijaya, Kristian Florensio (STAIN Sultan Abdurrahman Kepulauan Riau, 2022)
Perhaps, one of the most well-articulated hurdles daunting globalized EFL learners’ academic literacy dynamics can be attributed to foreign language reading anxiety. Under the massive expansion of foreign language reading anxiety, EFL learners commonly experience a higher level of perturbation while attempting to comprehend the contents forming in their specific reading texts due to the inevitable complexities presented during this process. This current small-scale library study aimed to exhaustively investigate particular effective strategies to overcome foreign language reading anxiety among globalized EFL learners to provide some illuminations for ELT experts, practitioners, and educators to devise more sophisticated reading strategies that can potentially alleviate foreign language reading anxiety. There were three main themes inferred in this present small-scale qualitative study namely: (1) The internalization of more comprehensible reading materials, (2) the promotion of more enjoyable reading circumstances, and (3) the inducement of more relevant reading strategies. For the future betterment of worldwide L2 reading enterprises, second language teachers are strongly commissioned to identify particular situations provoking excessive foreign language reading anxiety among EFL teachers in order to progressively design more authentic and meaningful reading activities.